Personal Higiene, Ketersediaan Air, dan Sanitasi Lingkungan dengan Kejadian Stunting pada Balita Usia 6–59 Bulan di Wilayah Kerja Puskesmas Singorojo I, Kabupaten Kendal: Personal Hygiene, Water Availability, and Environmental Sanitation with the Incidence of Stunting in Toddlers Aged 6–59 Months in the Working Area of the Singorojo I Public Health Center, Kendal Regency - Veramita Nanda Pradana; Suparmi Suparmi; Ratnawati Ratnawati (Amerta Nutrition, 2023)
Backgrounds: Stunting is a chronic nutritional problem in Indonesia. The increase in the incidence of stunting in Indonesia is influenced by various factors such as maternal, nutritional, socioeconomic, and environmental factors. Personal hygiene of mothers and children, access to basic sanitation, and clean water are associated with high stunting rates in the Singgorojo 1 Public Health Center. Objectives: Determined the relationship between personal hygiene, water availability, and environmental sanitation with the incidence of stunting in toddlers aged 6–59 months. Methods: Observational analysis used a case-control design. Data were collected through interviews using questionnaires and observation of children. The affordable population of this study was toddlers aged 6-59 months in the working area of ​​the Singgorojo Health Center 1. The sample used was 50 toddlers aged 6-59 months. The sampling technique was carried out by consecutive sampling. Data analysis used Chi-Square, Fisher Exact, and Logistic Regression tests. Results: The relationship between personal hygiene (OR=5.762; p=0.012; 95% CI=1.363–24.362), water availability (OR=4.571; p=0.349; 95% CI=0.473–44.170), and environmental sanitation with stunting incidence ( OR=9.333; p=0.001; 95% CI=2.431–35.839). The results of the multivariate analysis of the relationship between personal hygiene (OR=3.867; p=0.111; =1.353; 95% CI=0.732–20.423), water availability (OR=10.305; p=0.066; =2.333; 95 % CI =0.858–123.732), and environmental sanitation with stunting incidence (OR=10.535; p=0.002; =2.355; 95% CI=2.419–45.887). Conclusions: Personal hygiene and environmental sanitation are associated with stunting in toddlers aged 6–59 months.